2005
DOI: 10.1523/jneurosci.1100-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Visceral and Somatic Pain Processing in the Human Brainstem Using Functional Magnetic Resonance Imaging

Abstract: Evidence from both human and animal studies has demonstrated a key role for brainstem centers in the control of ascending nociceptive input. Nuclei such as the rostral ventromedial medulla and periaqueductal gray (PAG) are able to both inhibit and facilitate the nociceptive response. It has been proposed that altered descending modulation may underlie many of the chronic pain syndromes (both somatic and visceral). We used functional magnetic resonance imaging to image the neural correlates of visceral and soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
159
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(177 citation statements)
references
References 66 publications
18
159
0
Order By: Relevance
“…This suggests that the vlPAG maybe involved in these processes and would certainly tie in with the hindbrain connectivity seen, relating to anxiety and aversion processing. Interestingly, these findings correlate with human fMRI studies of visceral and somatic pain processing [Dunckley et al, 2005], where correlation between PAG activation and anxiety was observed during visceral pain (vlPAG processed) but not during somatic pain (dlPAG processes).…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that the vlPAG maybe involved in these processes and would certainly tie in with the hindbrain connectivity seen, relating to anxiety and aversion processing. Interestingly, these findings correlate with human fMRI studies of visceral and somatic pain processing [Dunckley et al, 2005], where correlation between PAG activation and anxiety was observed during visceral pain (vlPAG processed) but not during somatic pain (dlPAG processes).…”
Section: Discussionsupporting
confidence: 82%
“…RVM on-cells are directly inhibited by opioids, and it is suggested that these cells express mu-opioid receptors [38]. Moreover, increased RVM neuronal responses to noxious stimuli observed in human imaging studies indicate on-cell activity [39,40]. Therefore, we suggest that decreased responses in the RVM observed in the present study reflect inhibited on-cell activity through the AAR system activation.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to its modulating influence on pain (Dunckley et al, 2005), the PAG, through opioidergic mechanisms, suppresses respiration (Sessle et al, 1981) via direct actions on the nucleus tractus solitarius in the ventral lateral medulla. The PAG is connected to the prefrontal cortex (Hadjipavlou et al, 2006), in which we have identified breath hold-related BOLD signal decreases.…”
Section: Opioid-sensitive Aspects Of the Breath Holdmentioning
confidence: 99%